( | 2 | m | − | 3 | ) | ÷ | 5 | = | ( | 2 | ÷ | 3 | ) | m | − | 3 |
Left side of the equation = | 2 | m | × | 1 5 | − | 3 | × | 1 5 |
= | 2 5 | m | − | 3 5 |
2 5 | m | − | 3 5 | = | ( | 2 | ÷ | 3 | ) | m | − | 3 |
Right side of the equation = | 2 | ÷ | 3 | × | m | − | 3 |
= | 2 3 | m | − | 3 |
2 5 | m | − | 3 5 | = | 2 3 | m | − | 3 |
2 5 | m | − | 2 3 | m | = | - | 3 | + | 3 5 |
- | 4 15 | m | = | - | 3 | + | 3 5 |
- | 4 15 | m | = | - | 12 5 |
12 5 | = | 4 15 | m |
4 15 | m | = | 12 5 |
m | = | 12 5 | ÷ | 4 15 |
= | 12 5 | × | 15 4 |
= | 3 | × | 3 |
m | = | 9 |